Sodium–glucose cotransporter 2 inhibitors reduce day‐to‐day glucose variability in patients with type 1 diabetes - Koki Chiba; Hiroshi Nomoto; Akinobu Nakamura; Kyu Yong Cho; Kumiko Yamashita; Yui Shibayama; Aika Miya; Hiraku Kameda; Yoshio Kurihara; Shin Aoki; Tatsuya Atsumi; Hideaki Miyoshi (Journal of Diabetes Investigation, 2021)
Abstract Aims/Introduction Sodium–glucose cotransporter 2 inhibitors (SGLT2i) are used worldwide because of their multiple benefits for patients with type 2 diabetes. The purpose of this study was to determine the efficacy and safety of SGLT2i in patients with type 1 diabetes. Materials and Methods Patients with type 1 diabetes who had been treated with SGLT2i for >12 weeks were included in this retrospective observation study. We recorded the changes in body mass, insulin dose, blood and urine test data, and adverse events. The changes in day‐to‐day glucose variability, as the primary end‐point, was evaluated using the interquartile range (P25/P75) of the ambulatory glucose data obtained using continuous glucose monitoring. Results A total of 51 patients (37 women; mean age 52.7 years) were included. Glycated hemoglobin and body mass significantly decreased by 0.4% and 1.6 kg, respectively. The total required insulin dose decreased by 9.4% (42.7 ± 26.6–38.7 ± 24.3 units/day). Continuous glucose monitoring data were obtained from 30 patients. P25/P75 decreased by 17.6 ± 20.7% during SGLT2i treatment (P < 0.001). The percentage of time per day within the target glucose range of 70–180 mg/dL significantly increased (from 42.2 to 55.5%, P < 0.001), without an increase in the percentage of time spent in the hypoglycemic range (<70 mg/dL). Urinary ketone bodies were detected in four patients (7.8%), but none developed ketoacidosis. Conclusions SGLT2i improved day‐to‐day glucose variability and time in the target glucose range, without increasing frequency of hypoglycemia, in patients with type 1 diabetes, and reduced glycated hemoglobin, body mass and the required insulin dose.